POTENSI CERITA RAKYAT “KI AGENG MANGIR” SEBAGAI BAHAN AJAR PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Hari Kuncoro; Jeffry Handhika; Aris Wuryantoro (CV Edujavare Publishing, 2026)
The integration of local wisdom through folklore into learning can strengthen students' character education in a contextual manner. This study aims to identify the character education values contained in the folk story